Breve nota sobre la estructura tradicional de la forma del poder (2011)
In the first place, this article aims to link Ralph Dahrendorf’s ethnological analysis on the traditional power structure with the acute approach to the “State’s types” (classified according to the preponderance of one or another function of the political power) proposed by Carl Schmitt. Finally the author points out how the western medieval political order was founded upon a traditional forma mentis, which contrasts with the rationalist mentality of modern Enlightenment.